Pengaruh Model Pembelajaran Di Luar Kelas Terhadap Hasil Belajar Siswa Kelas III Dalam Menulis Laporan Di UPT SDN 177 Gresik - muniroh, lu'luil; Ghufron, Syamsul; Thamrin Hidayat, Muhammad; Kasiyun, Suharmono (Faculty of Engineering, Wijaya Putra University, 2022)
This research is focused on the problem of student learning outcomes of class III UPT SDN 177 Gresik in writing reports that are classified as low by applying the learning model outside the classroom. This research is a quantitative research with a one-group pretest-posttest design method. The population in this study consisted of 27 students, namely 9 males and 18 females. The sample of this study used a full sampling technique. The results obtained are based on the students’ increasing average scores and the results of the paired sample t-test. The results of this study proved to increase from the average value of 58,89 students increased to 83,52 and the paired sample t-test test that the value of tcount is greater than ttable (th = 4,825 > tt=1,7033), in other words H1 is accepted and H0 is rejected.